112 Sculptures Petit Format. - Léonard, René; Théâtre National Bruxelles (Brussel : Théâtre National Bruxelles, 1972)
Anthoons, Willy ; Arnould, Marcel ; Bury, Pol ; Caille, Pierre ; Claus, Louis ; Courtois, Albin ; Dekeijser, André ; Effront, Nadine ; Gangolf, Serge ; Ghysels, Jean-Pierre ; Glibert, Jean ; Grard, Georges ; Guebbels-Dervichan, M. ; Guilmot, Jacques ; Haar, Marie-Paule ; Henrion, Joseph ; Hensen, Stan ; Laenen, Jean-Paul ; Lapaille, Monique ; Lenaerts, Henri ; Leplae, Charles ; Leroy, Christian ; Moeschal, Jacques ; Reinhoud ; Renard, Michel ; Roulin, Félix ; Smolders, Michel ; Souply, Emile ; Stievenart, Michel ; Strebelle, Olivier ; Vandercam, Serge ; de Vinck, Antoine ; Willequet, André ; Wybaux, Fritz
biog. per kunstenaar
Frans
112 sculptures petit format, Théâtre National Bruxelles, mei - juni 1972
boek